EFFECT OF PROTEIN UNDEGRADED SUPPLEMENTATION ON PRODUCTION AND COMPOSITION OF MILK IN DAIRY COWS - Widyobroto, B.P.; Budhi, S.P.S.; Agus, A. (Diponegoro University, 2010)
This research was aimed to examine the effect of undegraded protein supplementation on nutrientsintake, production and milk composition in dairy cows. The purpose of this research was to provideinformation on the undegraded protein supplementation to increase milk production and composition indairy cows. The research was conducted for 3 months in Boyolali-Central Java. The study used 20lactation cows (<3 months of lactation), aged 3 to 3.5 years with body weight from 350 to 400 kg. Thecows were then randomly divided into 2 groups of ten based on their body weight, milk production,lactation period and age. The first group (control) and the second group (treated), both were fed dietbased on NRC (1987). The second group was added undegraded protein (UDP) of 30 g/l milk that mixedby concentrate. The observed variables were dry matter intake (DM), organic matter (OM), crudeprotein (CP), neutral detergent fiber (NDF), milk production and milk composition including fat, proteinand solid non fat (SNF). Data obtained were examined by t-test.The results showed that intake of DM, OM, and the NDF of treated and control groups were notdifferent (9.57; 8.49; 4.98 vs 9.44; 8.38; 5.40 kg/cow/d, respectively); however, protein intake of treatedgroup was higher (P<0.01) than that of the control group (1097 vs. 1210g/cow/d). Milk production ofcows receiving UDP supplementation tended to be higher than that in the control group (+ 1:45kg/cow/d). Although they tended to be lower in fat (4.13 vs. 3.88%), protein (2.45 vs. 2.27%) and SNF(7.26 vs. 6.94%), but protein and fat production were higher for cows receiving UDP supplementation(366 each; 214 vs. 330; 196g/cow/d). It can be concluded that UDP supplementation increased milk, fatproduction and milk protein but it tended to reduce the level of fat, protein and SNF milk.